2019
DOI: 10.1590/1806-9282.65.7.977
|View full text |Cite
|
Sign up to set email alerts
|

Renal angiomyolipoma

Abstract: SUMMARY INTRODUCTION Angiomyolipoma is one of the most common benign solid renal tumors. We investigated the characteristics of renal angiomyolipomas and the clinical outcomes of patients in the last thirteen years. METHODS The medical records of the patients who underwent nephrectomy were reviewed retrospectively from July 2005 to May 2018. The laboratory data, radiology, and pathology reports were recorded. Patients diagnosed with angiomyolipoma were included in the study. RESULTS A total of 28 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
1
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 14 publications
0
26
1
1
Order By: Relevance
“…Renal angiomyolipoma was first defined by Fischer in 1911, which predominantly affects females rather than males [ 8 ]. Some studies have suggested that AMLs can present in a wide age range from 19 to 93 years with overall prevalence being as high as 0, 3% [ 1 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Renal angiomyolipoma was first defined by Fischer in 1911, which predominantly affects females rather than males [ 8 ]. Some studies have suggested that AMLs can present in a wide age range from 19 to 93 years with overall prevalence being as high as 0, 3% [ 1 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) has a high sensitivity for detecting fat tissues, so it is useful to differentiate AML from other renal masses . However, MRI has a high cost and is time-consuming when compared to ultrasonography and CT [ 8 ]. Angiography of the renal artery is a useful invasive method to provide obscure anatomical data and to treat the corresponding causes of bleeding [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Angiomyolipoma is one of the most common benign renal tumors and accounts for 0.3-3% of all renal masses. [1] It contains fat, blood vessels, and smooth muscles in different proportions. [2] It mainly includes two histology types: classical and epithelioid [3] .…”
Section: Discussionmentioning
confidence: 99%
“…These can show predominance of smooth muscle elements or adipose tissue, depending on which it can be labelled as leiomyoma-like or lipoma-like. 2 In a recent study by Çalışkan et al 9 the authors described 28 cases of renal AMLs and classified in three categories: fat-rich (82.1%), fatpoor (14.3%) and epithelioid (3.6%). In the study by Aydin et al 3 classic AMLs accounted for 76.8% cases while epithelioid variants, epithelial cysts and microscopic AMLs were noted in 7.7% cases, 6.7% cases and 10.8% cases, respectively.…”
Section: Discussionmentioning
confidence: 99%